2019
DOI: 10.1167/19.14.4
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving your hand moving: BOLD suppression in sensory cortices and the role of the cerebellum in the detection of feedback delays

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 113 publications
(149 reference statements)
11
53
2
Order By: Relevance
“…Since the processing of sensory information of both action and feedback is suppressed during active movements, it is likely that the temporal comparison between action and feedback is affected as well. While the behavioral effects in the current experiment replicate previous results showing worse delay detection performances for actively compared to passively generated movement feedback (Arikan et al, ; Pazen et al, ; van Kemenade et al, ), it contradicts studies reporting enhanced detection performances during active versus passive movements (Schmalenbach, Billino, Kircher, van Kemenade, & Straube, ; Shimada, Qi, & Hiraki, ; van Kemenade et al, ). Importantly, studies showing enhancement effects have used button presses producing briefly displayed action outcomes presented at the end of the movement.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Since the processing of sensory information of both action and feedback is suppressed during active movements, it is likely that the temporal comparison between action and feedback is affected as well. While the behavioral effects in the current experiment replicate previous results showing worse delay detection performances for actively compared to passively generated movement feedback (Arikan et al, ; Pazen et al, ; van Kemenade et al, ), it contradicts studies reporting enhanced detection performances during active versus passive movements (Schmalenbach, Billino, Kircher, van Kemenade, & Straube, ; Shimada, Qi, & Hiraki, ; van Kemenade et al, ). Importantly, studies showing enhancement effects have used button presses producing briefly displayed action outcomes presented at the end of the movement.…”
Section: Discussioncontrasting
confidence: 58%
“…In line with this, it has been demonstrated that actively relative to passively generated sensory input is associated with less neural processing (suppression effect), in auditory (e.g., Heschl's gyrus), somatosensory (e.g., postcentral gyrus), and visual (e.g., calcarine sulcus) areas for discrete actions (Blakemore, Wolpert, & Frith, ; Straube et al, ). Similar effects were reported in visual and somatosensory cortices as well as the right posterior superior temporal sulcus for continuous action feedback such as videos of a moving hand (Arikan et al, ; Limanowski, Sarasso, & Blankenburg, ; Pazen et al, ).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Thus, visual information can be used to generate somatosensory predictions for the control of reaching and grasping. Arikan et al (2019) also demonstrate the multisensory nature of suppression during self-generated movements. They found reduced blood oxygenation level dependent (BOLD) activity in somatosensory, visual, and auditory regions during self-generated movements (vs. passive, externally generated movements).…”
Section: Predicting the Consequences Of One's Own Actionsmentioning
confidence: 70%